The Middle-Class Entrepreneurial Elite in Šibenik and Split (15th Century) (Povijesni prilozi (Historical Contributions), 2019)
The paper explores the business elite of late medieval Šibenik and Split based on examples of prominent entrepreneurs from historical records preserved in Šibenik and Split notary offices.